Field Work Practice Of Culinary Student Through Teaching Factory At SMK Negeri 1 Lubuk Sikaping - Tri Arina; Ezi Anggraini; Asmar Yulastri; Cici Andriani (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
Vocational High Schools (SMK) are required to produce graduates who are job-ready and equipped with skills that meet industry needs. SMK Negeri 1 Lubuk Sikaping, as one of the Centers of Excellence (SMK PK), is committed to developing its curriculum and providing learning facilities that equip students with the competencies needed for the workforce through the implementation of Teaching Factory learning. This study aims to determine the effect of Teaching Factory learning on the Readiness of Culinary Students' Field Work Practice at SMK Negeri 1 Lubuk Sikaping. This type of research uses a quantitative. The data collection technique was carried out through a questionnaire given to 66 students. Data analysis used software SPSS versi 26.00 with a simple linear regression test. The results of the study showed: (1) Teaching Factory learning is in the good category (44%), and Culinary Students' Field Work Practice Readiness is also in the good category (38%). (2) The results of the regression test show that there is a positive and significant influence between Teaching Factory learning on Field Work Practice, with a significance value of 0.010. (3) The regression coefficient value is 0.143, which means that every one unit increase in the TeFa learning variable can increase Culinary Students' Field Work Practice Readiness by 0.143 points. The R value of 0.143 indicates that Teaching Factory learning contributes 14.3% to Culinary Students' Field Work Practice Readiness, while the remaining 85.7% is influenced by other factors.